2016
DOI: 10.1021/acs.energyfuels.6b02803
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Torrefaction in the Wood Pellet Industry: A Critical Review

Abstract: As an established bioenergy industry, the global wood pellet sector is ideally positioned to adopt biomass torrefaction technologies. In this review, potential benefits and challenges of integrating torrefaction within the pellet industry are reviewed and the required technological interventions to enable this integration are analyzed. It is apparent that integration would accelerate the commercialization of biomass torrefaction and benefit the wood pellet industry, torrefaction developers, as well as coal-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 101 publications
3
63
2
1
Order By: Relevance
“…However, pellet properties had been determined for similar advice used by Mani et al [50], Rhen et al [51], and Carone et al [33]; they had demonstrated the reproduction of the conditions of the industrial process of pellet fabrication, and they can be implemented in an industrial application [52,53]. …”
Section: Optimal Conditions For the Biomass Torrefaction Of Reforestamentioning
confidence: 99%
“…However, pellet properties had been determined for similar advice used by Mani et al [50], Rhen et al [51], and Carone et al [33]; they had demonstrated the reproduction of the conditions of the industrial process of pellet fabrication, and they can be implemented in an industrial application [52,53]. …”
Section: Optimal Conditions For the Biomass Torrefaction Of Reforestamentioning
confidence: 99%
“…However, the bulk density of the torrefied biomass is low, even lower than the raw biomass itself, which makes the transportation and handling economically challenging . Consequently, integrating torrefaction with densification process such as pelletizing can solve challenges in storing and transporting biomass and facilitate a feasible use of the torrefied biomass as bioenergy commodity . In this context, the first pathway involves torrefaction followed by pelletizing process (TOP process) .…”
Section: Introductionmentioning
confidence: 99%
“…Here, pelletizing power consumption is increased due to the reduced water content and the brittle nature of the torrefied biomass while the grinding power consumption is decreased when it is used as pulverized solid fuel . In the second pathway, pelletizing is followed by torrefaction (TAP process) . In this process, pelletizing of raw material is possible without adding binding agents, the torrefied pellets stay intact and could facilitate handling, feeding, and safe torrefaction operation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although torrefaction technology is well developed, it has not yet moved to the commercial market. The consensus is that the main hindrance to the commercialization of this technology is the use of high-cost woody biomass as a feedstock (Kumar et al, 2017;Radics et al, 2017).…”
Section: Introductionmentioning
confidence: 99%